Comparison between the Effect of External or Internal Catheter on the Hospitalization Time, Drain Leakage, and Postoperative Complications in Patients Undergoing Radical Cystectomy with Orthotopic Neobladder - Mohamadhosein Izadpanahi; Sobhan Sabzi; Amid Yazdani (مجله دانشکده پزشکی اصفهان, 2018)
Background: The aim of this study was to compare the effect of internal catheter insertion with external catheter on the duration of hospitalization, drain leakage rate, and postoperative complications in patients with bladder cancer undergoing neoplasia radical cystectomy with orthotopic neobladder referring to Alzahra and Noor hospitals in Isfahan, Iran, during the years 2016-18.